IDENTIFIKASI MISKONSEPSI SISWA SMAN SE-KECAMATAN TAMPAN PEKANBARU PADA MATERI ELASTISITAS DAN HUKUM HOOKE - Nisa Febriana; Fakhruddin Fakhruddin; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This purpose of the research is to know the tier of student misconception in elasticity material and Hooke law. The research is done in SMAN Tampan Pekanbaru which consisted of SMAN 12 Pekanbaru and SMAN 15 Pekanbaru with a total subject of 70 students. This research is a survey research. The research design is carried out by taking information or data directly of the sample. Data collecting was done by test method, which is a four-tier diagnostic test. The first tier, students must answer the multiple choice questions that have been provided totaling 28 questions. The second tier, students must include the tier of confidence in answering the question. The third tier, students must choose the right reasons or write their own reasons in answering the questions. The fourth tier, students must include the tier of confidence in determining the reason. Data analysis was done descriptively. The result is showing the average pescentage of student misconception in indicator 1 was 31% (medium), on the indicator 2 was 43% (medium), on indicator 3 was 47% (medium), on indicator 4 was 51% (medium), on indicator 5 was 57% (medium) and on indicator 6 was 33% (medium). With thus it can be concluded that the tier of misconception of SMAN students Tampan Pekanbaru is in the medium category with an average percentage of 44%.Key Words: Misconception, Four-Tier Diagnostic Test, Elastisity And Hooke Law